Arquitetura enquanto signo: três igrejas católicas de Oscar Niemeyer - Oliveira, Fernando Kennedy Braga (2020)
The meaning in architecture began to be investigated more intensively in the second half of the 20th century. During this period, facing the emergence of modernism and the idea of a strictly functionalist in architecture, some architects - in the light of communication and perception theories - argued that the senses, and meanings, are inherent in the architectural. These options still permeate the architectural environment in the 21st century. In this work, we investigate the senses of three Oscar Niemeyer’s churches: São Francisco de Assis Church (1940), Chapel of Nossa Senhora de Fátima (1958) and the Cathedral of Brasília (1958). For this, we divided the study into four parts: an investigation of the meaning in architecture through the theories of communication; the construction of procedures for reading architecture through the aspects of Peirce Semiotics signs; the presentation of tradition in Catholic churches; and the reading of the senses of those three churches of Niemeyer. Our analysis pointed out that the iconic aspects are the most predominant communicative phenomena of three churches of Niemeyer, and that their indexes and symbols are linked to tradition due to the movements between architects, clients and society in the construction and use of the churches.